Alternative Medicine for the Treatment of Psoriasis. Issue 4 (December 2013) - Zahir, Amir; Kaviany, Parisa; Ehrlich, Alison
The use of complementary and alternative medicine has an estimated prevalence of about 51% amongst patients with psoriasis. The relatively lower costs, perceived fewer side effects, and versatile use alone or in combination with standard psoriasis treatments have increased its appeal. Clinical trials and case reports have investigated the use of dietary supplements, herbs, gluten-free diet, acupuncture, psychotherapy, meditation, and hypnosis for the treatment of psoriasis. Fish oil, vitamin D, inositol, curcumin, indigo naturalis, Aloe vera, capsaicin, and Mahonia aquifolium have shown some efficacy in some of the clinical trials covered in this review. Gluten-free diets and the use of meditation and stress-reduction exercises also have shown to help improve the clinical symptoms of psoriasis. Knowledge of these treatments can help dermatologists educate their patients who are interested in alternative remedies for psoriasis.